2016
DOI: 10.1002/zaac.201600019
|View full text |Cite
|
Sign up to set email alerts
|

Host‐Guest Complexes of [TriPip222], the Piperazine Analogue of [2.2.2]: Prediction of Ion Selectivity by Quantum Chemical Calculations VIII[#]

Abstract: The selectivity of the cryptand [TriPip222], a per-aza analogue of cryptand [2.2.2], in which each of the linking arms contains a piperazine ring for the endohedral complexation of metal cations of the I, II, and III main groups and group 12 of the periodic table of elements, was predicted on the basis of DFT [B3LYP/LANL2DZp (LANL2DZp = LANL2DZ augmented with polarization functions on non-hydrogen atoms)] calculated structures and complex-formation en-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…This observation might explain why [Cs + &o-Me 2 -2.2.1] is the preferred species in experiments where o-Me 2 -2.2.1 and o-Me 2 -2.2.2 compete for Cs + .A nu nusual type of anisotropic long-range order was observed in the crystal structure of [Cs + &o-Me 2 -2.2.1]:t he presence of Cs À Fb onds between counteranion and cryptates results in the formation of ah elical coordination polymer (see the Supporting Information for the packing diagram).Because some of our experiments represent as toichiometrically unbiased [18] competition between two dynamic cryptands for am etal ion, we wanted to test, whether the observed trends could be rationalized by theory.Inafirst set of DFT-based (B3LYP/LANL2DZp) model equations (see the Supporting Information for details), we determined complexation energies for the combination of the cryptands o-Me 2 -1.1.0, o-Me 2 -1.1.1, o-Me 2 -2.1.1, o-Me 2 -2.2.1,a nd o-Me 2 -2.2.2 with five alkali metal ions. [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information).With the exception of two outliers ([Li + &o-Me 2 -1.1.1] and [Rb + ·o-Me 2 -1.1.1]), we observed good agreement between the trends in experiment (Figure 2a)and theory (Figure 2b). More importantly,t he relative binding energies do indeed allow rationalizing our findings on adaptive behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might explain why [Cs + &o-Me 2 -2.2.1] is the preferred species in experiments where o-Me 2 -2.2.1 and o-Me 2 -2.2.2 compete for Cs + .A nu nusual type of anisotropic long-range order was observed in the crystal structure of [Cs + &o-Me 2 -2.2.1]:t he presence of Cs À Fb onds between counteranion and cryptates results in the formation of ah elical coordination polymer (see the Supporting Information for the packing diagram).Because some of our experiments represent as toichiometrically unbiased [18] competition between two dynamic cryptands for am etal ion, we wanted to test, whether the observed trends could be rationalized by theory.Inafirst set of DFT-based (B3LYP/LANL2DZp) model equations (see the Supporting Information for details), we determined complexation energies for the combination of the cryptands o-Me 2 -1.1.0, o-Me 2 -1.1.1, o-Me 2 -2.1.1, o-Me 2 -2.2.1,a nd o-Me 2 -2.2.2 with five alkali metal ions. [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information).With the exception of two outliers ([Li + &o-Me 2 -1.1.1] and [Rb + ·o-Me 2 -1.1.1]), we observed good agreement between the trends in experiment (Figure 2a)and theory (Figure 2b). More importantly,t he relative binding energies do indeed allow rationalizing our findings on adaptive behavior.…”
mentioning
confidence: 99%
“…Because some of our experiments represent as toichiometrically unbiased [18] competition between two dynamic cryptands for am etal ion, we wanted to test, whether the observed trends could be rationalized by theory.Inafirst set of DFT-based (B3LYP/LANL2DZp) model equations (see the Supporting Information for details), we determined complexation energies for the combination of the cryptands o-Me 2 -1.1.0, o-Me 2 -1.1.1, o-Me 2 -2.1.1, o-Me 2 -2.2.1,a nd o-Me 2 -2.2.2 with five alkali metal ions. [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information).…”
mentioning
confidence: 99%
“…A naïve interpretation would be that the obtained ion selectivity is wrong in comparison to that calculated for Equation (1) and Equation (2). Keeping in mind that [TriPip222] has a larger cavity than 2 , the complexes best fit the next larger ions (K + before Na + , Sr 2+ and Ca 2+ before Ba 2+ ), which explains Figure nicely . The larger alkaline ions starting from potassium are too large and do not fit in 2 .…”
Section: Resultsmentioning
confidence: 86%
“…DEG = diethylene glycol. [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information).With the exception of two outliers ([Li + &o-Me 2 -1.1.1] and [Rb + ·o-Me 2 -1.1.1]), we observed good agreement between the trends in experiment ( Figure 2a)and theory (Figure 2b). In the corresponding experiment, we found that the dynamic system remained mainly at the [Li + &o-Me 2 -1.1.1] state,thus indicating that the cryptand o-Me 2 -1.1.0 is either too small to accommodate Li + or that binding to ah ost with one additional oxygen donor atom outweighs apossible preference for the smaller host.…”
mentioning
confidence: 99%
“…Ther esulting X-ray structures are depicted in Figure 1a, along with the structure of previously reported [Na + &o-Me 2 -1. [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information). [19] We also carried out NMR titrations for all 20 host-guest combinations,a swell as one representative isothermal titration calorimetry (ITC) study,w hich revealed that sodium binding to o-Me 2 -1.1.1 is driven both enthalpically and entropically (see the Supporting Information).…”
mentioning
confidence: 99%